Initial Soil Springs Stiffness for laterally loaded Piles - Bahrami, Amir; Nikraz, Hamid (The Australian Geomechanical Society and New Zealand Geotechnical Society, 2012)
Total number of 180 finite element models is created. Soil is modelled by three dimensional elastic isotropic brick elements with cylindrical shaft cavity at the centre. Pile is modelled with ordinary Euler- Bernoulli beam elements. Different connectivity scenarios between the soil and the pile surface are examined. Elastic properties of the soil are changed for each FE model within wide range of possible values. A globally covering database is created for free - head pile stiffness from FE analysis results. Lateral springs stiffness are calculated by equating pile head stiffness from FE models to predicted value from beam on elastic support theory. Spring’s stiffness is correlated to mechanical properties of the soil, shaft diameter, and pile flexibility factor using curve fitting techniques. It is found that spring stiffness is dependent to shaft diameter. It is also found that relative connectivity between the soil and pile’s skin, highly affects the spring’s stiffness. Comparison to work by other researchers is made.